Representações sociais sobre a violência nas escolas do campo do município de Cascavel, Paraná - Luz, Euzaide Claro da Silva da (2014)
This study aims to analyze, interpret and discuss the representations of school violence caused by social agents who work in two rural schools located in Cascavel / PR. The theory of social representations proposed by Pierre Bourdieu (1999b) was used here as the framework to guide the analysis. Data interpretation was done by means of a qualitative method. Semi-structured interviews were used for data collection. They were recorded and transcribed ipsis litteris. Fourteen social agents of the rural school participated in the research to compose the sample. There were seven agents from each school: two directors, two teachers, two pedagogues, two secretaries, two employees who do general services, two students and two parents of students. Results indicate that rural school violence is represented in every act committed, either at school or nearby, by the community agents, resulting in physical or psychological suffering in any participants of the community.